Jesuit Fathers Beyond the Iron Curtain: Directions and Challenges of Lithuanian Jesuit Exiles in the 20th Century - Stanevičius, Ignas (Lietuvos istorijos studijos, 2024)
The article examines the directions and challenges of the activities of Lithuanian Jesuits in exile from 1931 to 1990. The study utilizes archival Jesuit documents such as annual meeting reports, meeting protocols, correspondence, and memoirs. In 1948, with the approval of the Jesuit leadership in Rome, the Jesuits established a vice-province that brought together all the priests separated from the native Lithuanian Jesuit province. The challenges of emigration compelled the monks to adapt to the everyday life of the new world, nurture the spirit of Jesuit life, and preserve their national identity. Jesuits continued their missionary work beyond the borders of the vice-province, undertaking missions in Canada, South America, and Uruguay. The expansive geographical scope of their activities raised concerns regarding the spiritual calling of the Jesuits themselves. Simultaneously, the decrees of the Second Vatican Council had a parallel influence, prompting Jesuits to reconsider their affiliation with the order.
Keywords: Catholic mission; Catholic Church; Jesuits; diaspora; clergy